Calculation Method of Driving Force of the Plate Quantitative Conveyor Chain Drive System - Xi Qiming; Shang Shibo; Liu Jingxiong; Yuan Hua (Jixie chuandong)
For improving the stability and security when the plate quantitative conveyor start-up and the accelerating operation,the calculation problem of driving force of chain drive system is studied.The maximum static tension of the chain drive system on stable operating conditions is calculated by point by point calculation method.The multi-axis electric drive system conversion method is proposed and the acceleration load is calculated by converted the inertial resistance of linear moving parts and rotating parts to drive shaft.The maximum driving force is sum of maximum static tension and the acceleration load.The results show that,the acceleration load account for the driving force about 35%,the drive power and breaking force calculation is necessary to consider the impact of the acceleration load in addition to the maximum static tension.